DIFFERENCES IN GUT MICROBIOTA MODULATION BY SEMAGLUTIDE, LIRAGLUTIDE AND TIRZEPATIDE - Julia Nowakowska; Milena Krawczyk; Piotr Komasara; Tomasz Szwarc; Mateusz Kałwik; Paweł Mikołajczak; Aleksandra Płusa; Dominika Brożyna; Bartłomiej Sałapski; Dominika Żyła (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and purpose: Gut microbiota has emerged as a key regulator of metabolic homeostasis. Incretin-based therapies such as semaglutide, liraglutide and tirzepatide not only improve glycemic control and promote weight loss, but may also exert systemic effects through microbiota modulation. This narrative review aims to compare the gut microbiota-related effects of these agents based on current preclinical and clinical evidence. Material and method: A systematic search of PubMed and Web of Science databases was conducted for full-text studies published between 2020 and 2025. Inclusion criteria encompassed original research in humans and animals evaluating the impact of semaglutide, liraglutide or tirzepatide on gut microbiota. From 136 initial results, 30 eligible studies were included after removing duplicates and applying inclusion criteria. Results: All three agents promoted increases in beneficial taxa such as Akkermansia muciniphila and SCFA-producing bacteria, and reduced pro-inflammatory genera. Semaglutide was associated with neuroimmune modulation, liraglutide with renal and hepatic benefits, while tirzepatide induced broader taxonomic shifts and diversity restoration, likely due to dual receptor agonism. Most findings derive from animal models, with limited human data available. Conclusions: Semaglutide, liraglutide and tirzepatide demonstrate both shared and distinct microbiota-modulating properties, which may partly mediate their therapeutic effects. Further clinical studies integrating microbiota profiling and metabolic outcomes are needed to validate these findings and support microbiota-informed treatment strategies.